2010
DOI: 10.1369/jhc.2010.954842
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fluorescence Imaging of Myelination

Abstract: S U M M A R Y We describe a novel fluorescent dye, 3-(4-aminophenyl)-2H-chromen-2-one (termed case myelin compound or CMC), that can be used for in situ fluorescent imaging of myelin in the vertebrate nervous system. When administered via intravenous injection into the tail vein, CMC selectively stained large bundles of myelinated fibers in both the central nervous system (CNS) and the peripheral nervous system (PNS). In the CNS, CMC readily entered the brain and selectively localized in myelinated regions suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…Our previous structure-activity relationship studies of coumarin derivatives led us to identify a lead compound, named Case Imaging Compound (CMC), which readily crosses the BBB and selectively binds to myelin sheaths in vivo. 17 We found that the structure of CMC can be selectively modified without adversely affecting its binding affinity and specificity for myelin. To develop a contrast agent for MR imaging, we explored the possibility of introducing a linker in the 3-position so that CMC could be conjugated to a gadolinium complex based on a DOTA derived monoamide macrocyclic ligand (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid).…”
Section: Introductionmentioning
confidence: 81%
“…Our previous structure-activity relationship studies of coumarin derivatives led us to identify a lead compound, named Case Imaging Compound (CMC), which readily crosses the BBB and selectively binds to myelin sheaths in vivo. 17 We found that the structure of CMC can be selectively modified without adversely affecting its binding affinity and specificity for myelin. To develop a contrast agent for MR imaging, we explored the possibility of introducing a linker in the 3-position so that CMC could be conjugated to a gadolinium complex based on a DOTA derived monoamide macrocyclic ligand (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid).…”
Section: Introductionmentioning
confidence: 81%
“…2A). Because of the quantitative limits of immunofluorescence techniques and the possibility that melanin autofluorescence might interfere with the analyses, we examined the same tissue biopsies using an infraredbased method, which allows for the quantitative comparison of normal and diseased skin (20). The results show that stage II melanoma lesions (21) were associated with significantly higher AC immunoreactivity, compared with normal skin or node-positive (stage III-IV, N1 or N2, M0, or M1) melanoma (Fig.…”
Section: High Ac Expression In Human Melanoma Cell Lines Andmentioning
confidence: 99%
“…Schmahl et al (1999) described staining of myelin in tissue sections using a cyanine dye 5,5'-diphenyl-9-ethyl-oxacarbocyanine (DEOC), and Xiang et al (2005) described the synthesis and characterization of two squarylium-based near infra-red myelin (NIM) dyes with selectivity for myelin. For in vivo imaging, Wang and colleagues described a number of fluorescent dyes including (E,E)-1,4-bis(4'-aminostyryl)-2-dimethoxy-benzene (BDB), 3-(4-aminophenyl)-2H-chromen-2-one (termed Case Myelin Compound), and 3,3’-diethylthiatricarbocyanine iodide (DBT), which penetrate the blood-brain barrier and bind selectively to myelin in the central and peripheral nervous systems (Wang et al, 2010; Wang et al, 2011; Wu et al, 2006). …”
Section: Introductionmentioning
confidence: 99%